KARAKTERISTIK KEPAILITAN BADAN HUKUM KOPERASI - RACHMAT SUHARTO (2019)
The title of this research is the bankruptcy characteristic of cooperative as legal entity This research focused as follows : (1) Philosophy of the establishment of a cooperative legal entity., (2) Characteristics of cooperative legal entities with other legal entities, (3) The cooperative's responsibility in the event of bankruptcy is associated with the characteristics of the cooperative legal entity. This research using statute approach, conceptual approach, and case approach. The results of the study show that the philosophy of the formation of a cooperative legal entity is an activity carried out by a group of people or groups that prioritize activities that are cooperative, mutual cooperation based on equality. Characteristics of cooperative legal entities can be seen from 3 (three) aspects, namely normative aspects, legal aspects and operational aspects. In the event of bankruptcy, the cooperative is responsible for settling the debts billed to him through the designated curator and for the members who have deposited their funds will be made settlement or settlement in the liquidation period before the dissolution is carried out on the cooperative and the obligation to achieve common goals namely welfare all members of the cooperative.